Quenching of dynamic nuclear polarization by spin–orbit coupling in GaAs quantum dots - Nichol, John M.; Harvey, Shannon P.; Shulman, Michael D.; Pal, Arijeet; Umansky, Vladimir; Rashba, Emmanuel I.; Halperin, Bertrand I.; Yacoby, Amir (Nature communications, 2015)
The central-spin problem is a widely studied model of quantum decoherence. Dynamic nuclear polarization occurs in central-spin systems when electronic angular momentum is transferred to nuclear spins and is exploited in quantum information processing for coherent spin manipulation. However, the mechanisms limiting this process remain only partially understood. Here we show that spin–orbit coupling can quench dynamic nuclear polarization in a GaAs quantum dot, because spin conservation is violated in the electron–nuclear system, despite weak spin–orbit coupling in GaAs. Using Landau–Zener sweeps to measure static and dynamic properties of the electron spin–flip probability, we observe that the size of the spin–orbit and hyperfine interactions depends on the magnitude and direction of applied magnetic field. We find that dynamic nuclear polarization is quenched when the spin–orbit contribution exceeds the hyperfine, in agreement with a theoretical model. Our results shed light on the surprisingly strong effect of spin–orbit coupling in central-spin systems. Dynamic nuclear polarization is the transfer of electronic angular momentum to nuclear spins and is a potential route for coherently manipulating spin in quantum information. Here, the authors show that spin–orbit coupling can quench dynamic nuclear polarization in a gallium arsenide quantum dot.